Effects of Exercise or Physical Activity on Overweight and Obese Individuals With Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-analysis - Ba Armah, Shaymaa M (My University, 2018)
Rationale: The prevalence of obesity among individuals with chronic obstructive pulmonary disease (COPD) is increasing, which contributes to further ventilatory limitations, and compromised exercise capacity, and health-related quality of life (HRQOL) compared to COPD alone. Objective: To conduct a systematic review to evaluate the effects of exercise interventions on walking capacity, ventilatory parameters, anthropometrics and HRQOL in individuals with COPD and elevated weight. Methods: A search was conducted on March 16, 2018 of Embase, Medline, CINAHL, AMED and PsycINFO for controlled trials of exercise interventions, involving adults with any stage of severity and stability of COPD with concurrent obesity or overweight. Overall effects were determined with standardized (SMD) and weighted (WMD) mean difference, using Review Manager 5.3. Results: Nineteen studies with 1716 participants (BMI mean ± SD 28.2 ± 5.1 kg/m2) were included. Exercise interventions were effective in improving walking capacity measured by the 6-Minute Walk Test (6MWT), Endurance Shuttle Walk Test and Incremental Shuttle walk Test (12 studies, 1215 participants, SMD 0.25 (95% CI [0.06, 0.43]); p=0.01), fat-free mass index (2 studies, 285 participants, WMD 0.33 kg/m2 (95% CI [0.21, 0.46]); p<0.00001), St. George Respiratory Questionnaire (6 studies, 648 participants, WMD -7.49 points (95% CI [-13.01, -1.98]); p=0.008) and Chronic Respiratory Disease Questionnaire Dyspnea (5 studies, 478 participants, WMD 0.51 points (95% CI [0.00, 1.02]); p=0.05), Emotion (4 studies, 404 participants, WMD 0.28 points, 95% CI [0.03, 0.54]); p=0.03), and Mastery domains (4 studies, 404 participants, WMD 0.31 points (95% CI [0.02, 0.59]); p=0.03). There were no effects on ventilatory parameters or anthropometric measures. Conclusions: Exercise interventions were effective in improving walking capacity and HRQOL in individuals with COPD and elevated weight. There is an important opportunity to establish effective interventions to minimize the functional and health effects in this subset of the COPD population.
Keywords: Chronic Obstructive Pulmonary Disease; Exercise; Obesity; Overweight